Pericallosal Aneurysms: Effectiveness of Endovascular Management - Bonadio, Lucas Eduardo; Mello, Luis Renato Garcez; Boer, Vitor Hugo Tamiosso; Haas, Leandro Jose; Bernardes, Celso Itiberê Carvalho; De Lara, Danielle; Cabral, Filipe Laurindo; Peres, Gabriel Hoher; Lindner, Stephanie (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Objective Clarify the safety and efficacy of the endovascular treatment of distal anterior cerebral artery (DACA) aneurysms, reporting outcomes of the aneurysms coiled in our service were compared with series of microsurgical treatment. The impact of embolization on ruptured or unruptured aneurysms remains controversial according to the current data, considering aneurysm from this topography should be aggressively treated due to their high incidence of rupture, currently there is a tend to prefer endovascular treatment.Methods We conducted a retrospective cohort study with 1092 patients admitted with cerebral aneurysm from October 2005 to March 2015 in our service. There were 31 cases of DACA aneurysms treated with the endovascular technique. These were compared with same topography aneurysms underwent to clipping.Results A total of 21 (67%) of 31 cases presented with ruptured aneurysms, 13 (59%) suffered clinical or radiological vasospasms, with modified Rankin Scale (mRS) scores of 3–5 in 7 patients (31%), and 4 deaths (mRS 6), reaching 92% of occlusion at one year.Conclusion Endovascular approach is associated with high angiographic occlusion rates and security.
Keywords: pericallosal aneurysm; endovascular management